Analisis Troubleshooting pada Engine G3408 Generator Set Caterpillar - Hersalniar; Firdaus; Oong Hanwar; Hendri Candra Mayana; Yuli Yetri (Manutech : Jurnal Teknologi Manufaktur, 2020)
A research has been conducted about Troubleshooting that occurs in the Caterpillar Engine G3408 generator Set which aims to analyze the causes of the hydraulic lock and determine how to solve the problems that occur in the Caterpillar G3408 Engine Generator Set. The research method is to perform detection, diagnostic, and repair on the engine by doing a visual check, looking for the root of the problem and doing the test. The results are engine has a hydraulic lock caused by a damaged one of the components of the Air Intake and Exhaust System. The after cooler is also damaged due to its long service life, causing the coolant to enter the combustion chamber. From the overall analysis it is concluded that the cause of engine failure is one of the components is damaged due to a long service life and to overcome this is doing repair and replacement of components on the After cooler with new components and do the periodic maintenance on the Caterpillar G3408 Engine Generator Set.